"The canes of our fathers”: the Mock-heroic in Giuseppe Rovani’s Cento anni (Altre Modernità, 2025)
After a preliminary discussion regarding the role played by quotations and literary allusions in Cento anni, this essay aims to reconstruct in detail the characteristics in detail the characteristics of the mock-heroic style adopted by Giuseppe Rovani in the fourth and final period of the novel (set between 1820 and 1829). For this purpose, the essay is divided into three parts. The first part focuses on the dense “Premise” to the fourth period in which Rovani compares himself to Alessandro Tassoni, the inventor of the mock-heroic, a style that attracts the novelist because it helps him preserve the right distance from the narrated material in the context of contemporary events. The second part examines the lexicon and the style adopted in the novel to recall (and, at the same time, invent) the exploits of the Compagnia della Teppa. The final part discusses the ambivalent relationship between Rovani and the members of the Compagnia della Teppa, whose actions, conducted with “neither legal nor legitimate means”, are interpreted as an instinctive, almost involuntary adoption of the “old theory of summary justice”, a principle whose validity is demonstrated precisely by the events concerning the main character of the last period of the novel, Giunio Baroggi.
Keywords: Giuseppe Rovani; 19th Century Italian Novel; reception of Alessandro Tassoni